Improvement of Severe Gummy Smile by Botulinum Toxin Application and Gingivoplasty - Pedron, Irineu Gregnanin (Journal of Nepalese Society of Periodontology and Oral Implantology, 2018)
Currently, the search for aesthetic excellence has become the main objective in the dental treatment. The gummy smile is one of the complaints from the patients, since this situation may influence their self-esteem and social relationship. The development of new techniques, such as the application of botulinum toxin, may be a therapeutic option more conservative, in the treatment of gummy smile. The purpose of this article is to present a case of a patient with dentogingival discrepancy and severe gummy smile, who was treated with gingivoplasty and application of botulinum toxin in order to optimise the harmony of the smile.